Sosialisasi Perencanaan Sumur Resapan Kecamatan Biringkanaya - Purwanto, Purwanto; Ramli, Muhammad; Nur, Irzal; ., Sufriadin; Anas, Aryanti Virtanti; Widodo, Sri; S. Tui, Rini Novrianti; Amalia, Rizki; Hatta, Asta Arjunoarwan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
When there is a population increase within an area, it will be coincided with housing needs. The demand of residential area sometimes requires land conversion from various previous uses such as rice fields, swamps, and other rain catchment areas. This shift in land functions causes several problems, such as flooding in the rainy season, drought in the dry season, and other environmental problems, including the increasing household waste. This community service is conducted to socialize the planning of infiltration wells in Biringkanaya District. Mainly, this community service aims to increase the community's awareness regarding perodical flood disasters and surface water shortages around the area. Besides that, this community service also aims to socialize the use of infiltration wells as an attempt to manage water around the activity location. Several steps have been taken in order to achieve those goals. Those steps are surveying field conditions, taking out questionnaires, and public disseminating to the community and other stakeholders. The field survey shows that the flood occurs because the discharge of runoff water that falls into the rain catchment area is much greater than the discharge of runoff that comes out. Based on the analysis, planning and designing infiltration wells are imperative to accumulate ground water. After the dissemination, the level of public understanding of surface water conditions and the function of infiltration wells is increasing. The community provides input regarding planning for infiltration wells that can be utilized to manage household waste.